Authentic and Reliable Data in the Service of National Public Data Asset - Pálmai, Gergely; Csernyák, Szabolcs; Erdélyi, Zoltán (Public Finance Quarterly, 2021)
The analysis focused on how efficient management of the national data asset is supported by the Hungarian regulatory framework concerning the use of public information, and whether public data constituting part of the national data asset can be deemed authentic and reliable to support the efforts for the digitalisation and artificial intelligence-based developments of the public sector. The analysis shows why the availability of authentic and reliable data in terms of the national data asset has outstanding significance. In support of this assertion, it presents the different levels of data asset use, the role of using artificial intelligence in the public sector, and the significance, risks and challenges of the authenticity and reliability of public data, from both a data protection and a public finance aspect. Inaccuracy, unreliability of input data predestines the generation of incorrect result products (conclusion, decision), even if the appropriate algorithm is used, which could lead to direct financial loss, for both the citizens and the state. The authors of the analysis therefore suggest that a paradigm shift is necessary in the strategies targeting the efficient use of the public sector’s data, with the necessity to record the fundamental precondition that the national data asset must be based on reliable and authentic data.